Bespoke automation of medical workforce rostering using Google’s free cloud applications - Peter Benjamin Michael Thomas (Journal of Innovation in Health Informatics, 2017)
Background: Providing safe and consistent care requires optimal deployment of medical staff. Ensuring this happens is a significant administrative burden due to complex working patterns.